The perfect English grammar workbook: Simple rules and quizzes to master today's English - McLendon, Lisa (Berkeley : Zephyros Press, 2017)
Simple instructions followed by self-directed quizzes; RELEVANT, ENGAGING EXAMPLES that demonstrate grammar rules with wit, humor, and contemporary appeal; RECENT, UP-TO-DATE RULES based on the English language we use today; A WIDE VARIETY OF EXERCISES that make learning fun; HELPFUL FEATURES FOR CLASSROOM USE including standalone answer keys for easy photocopying and color-coded pages for quick navigation.
Keywords: To-read -- Education -- Academic Book